INNOVATION AND CHALLENGES IN ENGLISH LANGUAGE TEACHING WITHIN THE MERDEKA BELAJAR FRAMEWORK - Pratiwi, Widya Rizky (Publikasi dan UKI Press UKI Toraja., 2024)
This study investigates the imperative for innovation in English Language Teaching (ELT) within the framework of the Merdeka Belajar (Freedom to Learn) curriculum in Indonesia. The background underscores the transformative nature of the educational landscape due to the implementation of the Merdeka Belajar policy, necessitating adaptation and innovation from English language teachers. The aim of this research is to bridge the gap in literature by examining how teachers respond to the policy, identifying innovations, exploring challenges, and providing recommendations. Employing a descriptive qualitative methodology, data was systematically gathered from reputable sources and analyzed thematically. The findings reveal a pressing need for innovative teaching practices to align with the learner-centered approach advocated by the Merdeka Belajar policy. Despite the opportunities presented, challenges such as resistance to change, limited resources, and cultural barriers hinder implementation. The study contributes to the literature by providing insights into the innovative practices adopted by teachers and highlighting the challenges they face. Recommendations include focusing on professional development and addressing institutional and cultural constraints. In conclusion, this research underscores the critical need for ongoing innovation in English language teaching and calls for collective efforts to overcome challenges and maximize the benefits of the Merdeka Belajar curriculum